Numerical simulation of thermal processes in laser cladding of Al-50Si alloy on Al7075 surface - Kong, Meng (Nanyang Technological University, 2022)
The temperature field of laser cladding affects the stress field and microstructure of the formed part greatly, which directly determines the microstructure and mechanical properties of the formed part. However, it is very difficult to accurately measure and control the temperature of the laser melt pool and its surroundings in real time using the existing equipment. The development of numerical simulation provides a convenient and reliable method for the measurement of melt pool temperature. The numerical model established in this project will help the designers and process planners to have a better understanding of the complex cladding process and the influence of the several parameters involved. In actual industrial application, this will assist in developing optimal process planning solutions which was hard to get in usual methods. The laser cladding process of Al-50Si alloy on Al7075 surface was numerically simulated by ANSYS, considering the heat source model, latent heat of phase transition, surface effect element and so on. APDL command flow was selected to make the movement of heat source. Birth and death element method was used to simulate the formation of the cladding layer. The changing process of the temperature field during the entire laser processing process and the influence of the laser power on the maximum temperature were analyzed. Finally, the comparison between the simulation result and experimental result was carried out to verify the simulation.